Microbial biotransformation of beclomethasone dipropionate by Aspergillus niger - Saeed Ahmad; Farhan Hameed Khaliq; Asadullah Madni; Muhammad Nabeel Shahid; Irfan Pervaiz (Universidade de São Paulo, 2014)
In the present research, the steroidal anti-asthmatic drug beclomethasone dipropionate was subjected to microbial biotransformation by Aspergillus niger. Beclomethasone dipropionate was transformed into various metabolites first time from microbial transformation. New drug metabolites produced can act as new potential drug molecules and can replace the old drugs in terms of safety, efficacy, and least resistance. They were purified by preparative thin layer chromatography technique, and their structures were elucidated using modern spectroscopic techniques, such as 13C NMR, 1H NMR, HMQC, HMQC, COSY, and NOESY, and mass spectrometry, such as EI-MS. Four metabolites were purified: (i) beclomethasone 17-monopropionate, (ii) beclomethasone 21-monopropionate, (iii) beclomethasone, and (iv) 9beta,11beta-epoxy-17,21-dihydroxy-16beta-methylpregna-1,4-diene-3,20-dione 21-propionate.